Implementasi Metode Analytical Hierarchy Process (AHP) dalam Pemilihan Mahasiswa terbaik Program Studi E-Commerce Logistics di Politeknik Multimedia Nusantara - Mutia Zilan Syarqilah; Intan Nilam Cahya; Yose Aprian Simarmata; Aurella Wiga Andini; Dewi Hajar (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
The selection of the best students in higher education requires an objective and measurable assessment system because it involves many criteria. This study aims to design a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method for selecting the best students in the E-Commerce Logistics Study Program, Multimedia Nusantara Polytechnic. Data were obtained through interviews, paired comparison questionnaires, and institutional documents. The AHP method was implemented through hierarchical construction, paired comparisons, normalization, and consistency tests. The results showed that the Inspirer criterion had the highest weighting of 57.96%, followed by Improver 30.99%, and Pioneer 11.05%. All matrices had a Consistency Ratio (CR) value below 0.1, thus being declared consistent. Based on the final calculation results, Student V obtained the highest score of 1.06 and was recommended as the best student. The developed system is able to produce objective and transparent recommendations in the best student selection process.